Impact of library and information science research on development of policy documents as references - ibrahim, cecep (Bibliotecas. Anales de investigación, 2025)
Objective: Being referenced and cited by policy documents is crucial for demonstrating the social impact of research. This study aims to assess the impact of Library and Information Science (LIS) research on development of policy documents as references. Design/Methodology/Approach: The research method uses bibliometric and altmetric methods. The data for this study comprises LIS research indexed in Scopus and policy document data sourced from the Altmetric Explorer for Researchers, with data collection extending up to the year 2024. Results/Discusion: The findings show that Information Systems Research (229) is the LIS journal most frequently cited by policy documents. The Publications Office of the European Union is identified as the institution that most frequently produces policy documents citing LIS research. Additionally, the United States emerges as the country generating the highest number of policy documents citing LIS research Conclusions: Based on the findings, The impact of LIS research on development of policy documents as references remains suboptimal when compared to the volume of research published by LIS journals. Originality/Value. Enhancing the citation rate of LIS research by policymakers can be achieved by strengthening evidence, identifying topic trends, promoting open access, disseminating research on social media, and encouraging government efforts to emphasize the importance of using research as a reference in policy-making.